2010
DOI: 10.2119/molmed.2009-00168
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: PRAS40 is an mTOR binding protein that has complex effects on cell metabolism. Our study tests the hypothesis that PRAS40 knockdown (KD) in C2C12 myocytes will increase protein synthesis via upregulation of the mTOR-S6K1 pathway. PRAS40 KD was achieved using lentiviruses to deliver short hairpin (sh)-RNA targeting PRAS40 or a scrambled control. C2C12 cells were used as either myoblasts or differentiated to myotubes. Knockdown reduced PRAS40 mRNA and protein content by >80% of time-matched control values but di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Therefore mTORC1 phosphorylates PRAS40 to enhance protein synthesis and simultaneously to facilitate the assembly of the β subunits for forming immunoproteasomes [ 70 ]. Consistent with this report, PRAS40 deletion decreases protein synthesis in C2C12 myoblasts [ 53 ].…”
Section: Pras40 In Tumorsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore mTORC1 phosphorylates PRAS40 to enhance protein synthesis and simultaneously to facilitate the assembly of the β subunits for forming immunoproteasomes [ 70 ]. Consistent with this report, PRAS40 deletion decreases protein synthesis in C2C12 myoblasts [ 53 ].…”
Section: Pras40 In Tumorsupporting
confidence: 89%
“…Malla R et al reported that mTOR activation was increased in the liver tissues of PRAS40 knockout mice [ 44 ] (Figure 1A ). However, PRAS40 knockdown does not make any alteration on mTOR pathway in myoblasts [ 53 ].…”
Section: Pras40 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…5, A and B ). Phosphorylation of PRAS40, a regulator of mTORC1 and protein synthesis (36, 37), was less sensitive to insulin compared with protein synthesis per se (Fig. 5 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several well-described interactions are reconstructed. Furthermore, the inferred network also suggests new interactions between e.g., MTORC1 and proteins involved in translation via AKT1S1 36 indicating that this strategy might serve as an approach to extract new hypotheses about putative interactions.…”
Section: Pathway Analysis and Inference Of Interactions Between Mtor mentioning
confidence: 96%